Intragroup xenophobic attitudes, ethnic identity, and substance use among Latinx adolescents. Issue 3 (3rd August 2020) - Basáñez, Tatiana; Sussman, Steven; Clark, Jordan; Unger, Jennifer B.
Abstract: This study examined intragroup xenophobic attitudes, ethnic identity, and substance use ( N  = 905). Drawing on cognitive dissonance theory, we hypothesized that intragroup xenophobic attitudes among Latinx individuals would be associated with higher levels of substance use (SU) in early adulthood and that ethnic identity would increase the strength of that association. We found that in 10th grade, xenophobic attitudes were higher among respondents with lower ethnic identity, a longer family history in the United States, and less stress. In a longitudinal analysis, SU in emerging adulthood was highest among males, those reporting higher stress in 10th grade, and those with a longer family history in the United States. There was a significant interaction of ethnic identity and xenophobia on substance use ( β  = −.12, p  < .001), indicating that substance use was higher among Latinxs with low ethnic identity who harbor xenophobic attitudes. Findings are explained using system justification theory because intragroup xenophobia appears to operate as a coping strategy that is maladaptive for Latinx individuals reporting low ethnic identity but somehow useful to those with high ethnic identity.